2D Oxides for Electronics and Optoelectronics. Issue 8 (22nd June 2022) - Hu, Xiaozong; Liu, Kailang; Cai, Yongqing; Zang, Shuang-Quan; Zhai, Tianyou
Abstract : In recent years, 2D oxides have attracted considerable attention due to their novel physical properties and excellent stability. With the efforts of researchers, significant progress has been made in the synthesis and electronics and optoelectronics application of 2D oxides. Herein, a systematic review focusing on the preparation of 2D oxides and their applications in electronics and optoelectronics is provided. First, 2D oxides are summarized and classified according to their elements. Then, common preparation methods to synthesize 2D oxides including exfoliation, liquid‐phase synthesis, vapor deposition, surface oxidation of metal, and so on are introduced. Further, the applications of 2D oxides in electronics and optoelectronics are presented. Finally, the current challenges and envisioned development of 2D oxides are commented and prospected. Abstract : Due to the excellent properties and air stability, 2D oxides show promising application prospects in optoelectronics and electronics, which are expected to promote the development of the semiconductor industry together with common other 2D materials. Herein, the preparation and application in optoelectronics and electronics of 2D oxides in recent years are summarized.